Pyrolysis of Oxalate, Acetate, and Perchlorate Mixtures and the Implications for Organic Salts on Mars. Issue 4 (22nd April 2021) - Lewis, J. M. T.; Eigenbrode, J. L.; Wong, G. M.; McAdam, A. C.; Archer, P. D.; Sutter, B.; Millan, M.; Williams, R. H.; Guzman, M.; Das, A.; Rampe, E. B.; Achilles, C. N.; et al.
Abstract: Organic salts, such as Fe, Ca, and Mg oxalates and acetates, may be widespread radiolysis and oxidation products of organic matter in Martian surface sediments. Such organic salts are challenging to identify by evolved gas analysis but the ubiquitous CO2 and CO in pyrolysis data from the Sample Analysis at Mars (SAM) instrument suite on the Curiosity rover indirectly points to their presence. Here, we examined laboratory results from SAM‐like analyses of organic salts as pure phases, as trace phases mixed with silica, and in mixtures with Ca and Mg perchlorates. Pure oxalates evolved CO2 and CO, while pure acetates evolved CO2 and a diverse range of organic products dominated by acetone and acetic acid. Dispersal within silica caused minor peak shifting, decreased the amounts of CO2 evolved by the acetate standards, and altered the relative abundances of the organic products of acetate pyrolysis. The perchlorate salts scrubbed Fe oxalate CO releases and shifted the CO2 peaks to lower temperatures, whereas with Ca and Mg oxalate, a weaker CO release was observed but the initial CO2 evolutions were largely unchanged. The perchlorates induced a stronger CO2 release from acetates at the expense of other products. Oxalates evolved ∼47% more CO2 and acetates yielded ∼69% more CO2 when the perchlorates were abundant. The most compelling fits between our organic salt data and SAM CO2 and CO data included Martian samples acquired from modern eolian deposits and sedimentary rocks with evidence for low‐temperature alteration. Plain Language Summary: In our efforts to characterize indigenous Martian organic matter, we must contend with a near‐surface record that has been substantially altered by radiation and oxidation. Under such conditions, much of the surficial organic record on Mars may have decomposed into organic salts, which are challenging for flight instruments to conclusively identify. If organic salts are widespread on the Martian surface, their composition and distribution could offer insight into the less‐altered organic record at depth and they may play an important role in near‐surface carbon cycling and habitability. The organic detection techniques employed by the Mars Science Laboratory Curiosity rover include thermal extraction in combination with mass spectrometry. In this work, we used laboratory thermal extraction techniques analogous to those of the rover to examine organic salts as pure standards, as minor phases in a silica matrix, and in mixtures with O2 ‐evolving perchlorate salts. When we compared our results with flight data, we found that many of the CO2 profiles produced by our organic salt samples were similar to the CO2 evolutions observed by the rover. The best fits with our laboratory data included Martian materials acquired from modern eolian deposits and sedimentary rocks that had evidence for low‐temperature alteration. Key Points: Flight‐like thermal analyses of organic salts suggest such phases may have been present in many of the samples analyzed by Mars missions Perchlorates greatly impacted the thermal decomposition of organic salts and enhanced CO2 production at the expense of other products The most compelling hints of organic salts occurred in pyrolysis data from altered Martian sedimentary rocks and modern eolian deposits